Peran Bantuan Hukum Terhadap Tersangka Dalam Proses Penyidikan - Febrianto Gunawan; Kukuh Sudarmanto; Kadi Sukarna; Soegianto Soegianto (Jurnal USM Law Review)
This study aims to evaluate the effectiveness of legal assistance in the investigation process for economically disadvantaged suspects at the Semarang Police Department, with a focus on the challenges and solutions encountered. The criminal justice system in Indonesia regulates the rights of suspects, including the right to legal assistance. Although this right is governed by various laws and regulations, practices in the field reveal a gap between the expected norms and the reality. This research uses an empirical legal method with an empirical juridical approach, integrating the analysis of legal norms with their implementation in practice. The findings show that although the regulations related to legal assistance are generally applied, there are still significant obstacles related to public legal awareness and the lack of effective socialization. While law enforcement officers and legal aid institutions play an active role, there is still a need for improvements in facilities and legal education for the public to ensure that legal assistance is accessible to all levels of society. This study recommends improvements in the legal assistance system and an increase in public understanding of the importance of legal aid.